(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The paper projectsan in-depth insight into the psyche of the suppressed and the agonizedprotagonists who have suffered double oppression both from the white and hermale counterpart, and will deal with Walker’s common theme of thedestructiveness of racism and poverty, violence towards women and theirinherent resilience through their shared experience, which binds and draws themcloser together and how they find acceptance when they are in each other’scompany. It will focus on how Walker’s women characters are portrayed as ameans for women to summon the courage to share their own experience and stories,and how these stories allow women to resist oppression and dominance. It willfocus on their struggle against racist, sexual and violent society and theirinherent resilience incorporated in ‘The Color Purple’.